2011
DOI: 10.1016/j.ijsolstr.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical programming approaches for the safety assessment of semirigid elastoplastic frames

Abstract: a b s t r a c tThis paper presents two complementary mathematical programming based approaches for the accurate safety assessment of semirigid elastoplastic frames under quasistatic loads. The inelastic behavior of the flexible connections and material plasticity are accommodated through piecewise linearized nonlinear yield surfaces. As is necessary for this class of structures, geometric nonlinearity is taken into account. Moreover, only a 2nd-order geometric approximation is included as this is sufficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A conventional lumped plasticity model within a ''line'' finite element framework (e.g. Cocchetti and Maier, 2003;Tangaramvong and Tin-Loi, 2011) is adopted. Plasticity is thus accommodated through the traditional concept of the generalized plastic hinge model, for which the formation of such hinges is confined only to the member ends.…”
Section: Classical Limit Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A conventional lumped plasticity model within a ''line'' finite element framework (e.g. Cocchetti and Maier, 2003;Tangaramvong and Tin-Loi, 2011) is adopted. Plasticity is thus accommodated through the traditional concept of the generalized plastic hinge model, for which the formation of such hinges is confined only to the member ends.…”
Section: Classical Limit Analysismentioning
confidence: 99%
“…We have found that such reformulations are particularly effective for solving the MPECs that arise in engineering mechanics problems (e.g. Ferris and Tin-Loi, 2001;Tangaramvong and Tin-Loi, 2011). In the present work, we have adopted the socalled ''relaxation'' algorithm that performed remarkably well in solving block structures involving frictional contact (Ferris and Tin-Loi, 2001).…”
Section: Critical Post-collapse Analysis As An Mpecmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical programming is seemingly one of the most natural formalisms in which to cast the skeletal structures for determining the extreme dynamic response 12 . It readily offers an ideal framework capable of finite element modeling of structures, and also provides considerable physical insights into the dynamic behavior of structures 13 18 .…”
Section: Introductionmentioning
confidence: 99%